胆管细胞癌相关性缺血性卒中1例并文献复习 Cholangiocarcinoma-Associated Ischemic Stroke: A Case Report and Literature Review - 韦静雯，宋萍萍，丁燕，张玉生(WEI Jingwen, SONG Pingping, DING Yan, ZHANG Yusheng ) (Zhongguo cuzhong zazhi)
恶性肿瘤可明显增加缺血性卒中的发生风险，而缺血性卒中会加重肿瘤患者病情，是患者非肿瘤性死亡的重要原因。肿瘤相关性缺血性卒中（cancer-associated ischemic stroke，CAIS）发病机制复杂，预后差。早期识别和综合管理CAIS对改善患者预后有重要意义。本文报道1例胆管细胞癌相关性缺血性卒中病例的诊治过程，并结合文献复习，阐述CAIS的发病机制、临床特征、治疗与预后，为临床提供借鉴。 Abstract: Malignant tumors can significantly increase the risk of ischemic stroke, and ischemic stroke can exacerbate the condition of tumor patients, making it an important cause of non-neoplastic deaths. The pathogenesis of cancer-associated ischemic stroke (CAIS) is complex, with a generally poor prognosis. Therefore, early identification and comprehensive management of CAIS are of great significance for improving the prognosis of patients. This article reported the diagnosis and treatment process of a case of cholangiocarcinoma-associated ischemic stroke. Combined with literature review, the pathogenesis, clinical characteristics, treatment, and prognosis of CAIS were expounded, providing a reference for clinical practice.